Down-regulated Treg Cells in Exacerbated Periodontal Disease during Pregnancy - Hays, Aislinn (Int Immunopharmacol, 2019)
Pregnancy is a special period marked with complicated changes in various immune responses. Although pregnant women are prone to developing gingival inflammation, its immunological mechanism remains to be clarified. In a modified ligature-induced periodontal disease murine model, pregnant mice developed more severe alveolar bone loss. Using this model, we investigated the Treg responses during exacerbated periodontal disease in pregnant mice. We tested Treg-associated molecules in gingival tissues by quantitative real-time PCR and found decreased gingival expression of Foxp3, TGFβ, CTLA-4, and CD28 in pregnant mice after periodontal disease induction. We further confirmed that lower number of Treg cells were present in the cervical lymph nodes of pregnant periodontitis mice. Treg cells from the cervical lymph nodes of ligated pregnant mice and non-pregnant mice were tested for their suppressive function in vitro. We manifested that Treg suppressive function was also down-regulated in the pregnant mice. Additionally, we demonstrated that more inflammatory Th17 cells were present in the cervical lymph nodes of ligated pregnant mice. Therefore, impaired Treg development and function, together with upregulated Th17 response, may contribute to the exacerbated periodontal disease during pregnancy.